2011
DOI: 10.3386/w17295
|View full text |Cite
|
Sign up to set email alerts
|

Information Percolation in Segmented Markets

Abstract: We calculate equilibria of dynamic double-auction markets in which agents are distinguished by their preferences and information. Over time, agents are privately informed by bids and offers. Investors are segmented into groups that differ with respect to characteristics determining information quality, including initial information precision as well as market "connectivity," the expected frequency of their trading opportunities. Investors with superior information sources attain strictly higher expected profit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…Overall, we reject the null hypothesis of random trading patterns in transactions among market participants and we support trading models motivated by information flows (Babus and Kondor, 2016), information percolation (Duffie et al, 2015) and trading strategies (Kyle et al, 2016), which predict persistent trading patterns. To highlight this dynamic, we simulate an agent-based trading model, which replicates the contemporaneous correlations between financial and network variables, but exhibits no Granger-causality.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Overall, we reject the null hypothesis of random trading patterns in transactions among market participants and we support trading models motivated by information flows (Babus and Kondor, 2016), information percolation (Duffie et al, 2015) and trading strategies (Kyle et al, 2016), which predict persistent trading patterns. To highlight this dynamic, we simulate an agent-based trading model, which replicates the contemporaneous correlations between financial and network variables, but exhibits no Granger-causality.…”
Section: Introductionsupporting
confidence: 65%
“…Trading networks S127 information percolation/market connectivity (Duffie et al, 2015). 2 Each of these works serves to motivate an empirical examination of financial markets through the lens of network technology.…”
Section: Introductionmentioning
confidence: 99%
“…Appendices D through L are found in an online supplement, Duffie, Malamud, and Manso [16]. Appendices D through L are found in an online supplement, Duffie, Malamud, and Manso [16].…”
Section: Appendicesmentioning
confidence: 99%
“…In other social learning settings, previous research has found that public information releases may crowd out learning (e. g. Appendices D through L are located in an online supplement, Duffie, Malamud, and Manso [16]. Table 1 Directory of locations of proofs of main results.…”
Section: Appendicesmentioning
confidence: 99%
See 1 more Smart Citation